2016
DOI: 10.20473/jmtt.v9i3.3077
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Financial Attitude,Financial Knowledge, Parental Income Terhadap Financial Management Behavior

Abstract: The aim of this research is to obtain the knowledge regarding the influence of Financial Attitude, Financial Knowledge, and Parental Income toward Financial Management Behavior. This research conducted in Merauke, border area of Indonesia. Questionnaire is used to collect the data.The sample 382 respondents. Correspondence analysis and chi-square are used to analyze.The result of this research show that Financial Attitude has influence toward Financial Management Behavior while Financial Knowledge and Parental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
81
5
63

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(237 citation statements)
references
References 14 publications
14
81
5
63
Order By: Relevance
“…This research is supported research by Pradiningtyas and Lukiastuti (2019) which states that financial attitudes have a significant effect on financial management behavior, Herdjiono and Damanik (2016) state that financial attitude has a significant effect on financial management behavior, Mien and Thao (2015) states that a person's financial attitude has a significant effect on financial management behavior. Thus the hypothesis which states that financial attitude has a significant effect on financial management behavior is proven.…”
Section: Effect Of Financial Attitude On Financial Management Behaviormentioning
confidence: 68%
See 1 more Smart Citation
“…This research is supported research by Pradiningtyas and Lukiastuti (2019) which states that financial attitudes have a significant effect on financial management behavior, Herdjiono and Damanik (2016) state that financial attitude has a significant effect on financial management behavior, Mien and Thao (2015) states that a person's financial attitude has a significant effect on financial management behavior. Thus the hypothesis which states that financial attitude has a significant effect on financial management behavior is proven.…”
Section: Effect Of Financial Attitude On Financial Management Behaviormentioning
confidence: 68%
“…Lynne (2008) states that financial attitudes have a significant effect on financial management behavior while education level and financial knowledge does not affect financial management behavior. Prihartono and Asandimitra (2018) stated that financial knowledge, financial attitudes, and social demographics have a significant effect on financial deception behavior, while Herdjiono and Damanik (2016) stated that financial knowledge and parental income does not affect financial management behavior while financial attitudes have a significant effect on financial management.…”
Section: Introductionmentioning
confidence: 99%
“…Financial attitudes have an important role in determining a person's success or failure in managing their finances (Çoşkun & Dalziel, 2020). Coskun and Dalziel (2020) and Herdjiono and Damanik (2016) found that financial attitude affects financial behavior. Thus, the first hypothesis is as follow:…”
Section: Introductionmentioning
confidence: 99%
“…Semakin baik sikap keuangan pribadi seseorang maka semakin baik pengelolaan keuangannya. Hal tersebut sesuai dengan penelitian sebelumnya (Herdjiono, Damanik, and Musamus 2016) yang menyebutkan bahwa financial attitude memiliki pengaruh positif terhadap financial manajement behavior.…”
Section: Pendahuluanunclassified
“…Sejalan dengan penelitian Ida dan Dwinta (2010) yang menyebutkan bahwa financial knowledge memiliki pengaruh positif terhadap perilaku keuangan, dan didukung oleh penelitian yang telah dilakukan oleh Andrew dan Linawati (2014), (Amanah, Iradianty, and Rahardian 2016). Namun berbanding terbalik dengan (Herdjiono, Damanik, and Musamus 2016) yang mengatakan bahwa financial knowledge tidak mempengaruhi financial manajement behavior.…”
Section: Pengaruh Financial Knowledge Terhadap Keputusan Investasiunclassified